Ministry of housing utilities and urban communities ministerial decree no 67/2014 amending the executive regulation of the building law promulgated by ministerial decree no 144/2009 - Egypt (2025)
Ministry of Housing, Utilities and Urban Communities Ministerial decree no. 67 of the year 2014 وزارة الإسكان والنرافق والمجتمعات العمرانية قرار وزارى رقم 67 لسنة 2014